CONTROLE DE DOENÇAS NA CULTURA DA SOJA COM PRODUTOS ALTERNATIVOS - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2015)
The use of plant defense mechanisms inducers may increase the disease control spectrum in soybean. The objective of this study was to abiotic and biotic resistance inducers in experiments in detached leaves and field conditions in soybean. The experiments with detached leaves were conducted in the laboratory, since the field experiment was conducted at the Fazenda Escola Capão da Onça in the harvest 2013/2014. The experimental design for the experiment of detached leaves was completely randomized in a factorial arrangement (7 x 2), with five replications. The field experiment was adopted the design of a randomized block design with four replications. Treatments for the experiments were: 1 - control; 2 - acibenzolar-S-methyl (Bion 500 WG; 3 - calcium (Max Fruit; 4 - micronutrients: copper, manganese and zinc (Wert Plus; 5 - micronutrients: manganese, zinc and molybdenum (V6; 6 - NK fertilizer (Hight Roots; 7 - Ascophyllum nodosum (Acadian and 8 - azoxystrobin + cyproconazole (Priori XTRA with addition of Nimbus adjuvant. Were evaluated by the detached leaf method inducers against Phakopsora pachyrhizi, Sclerotinia sclerotiorum and Rhizoctonia solani. No difference in treatments for P. pachyrhizi. For Rhizoctonia solani and S. sclerotiorum was no difference highlighting treatment with A. nodusum and micronutrients: copper, manganese and zinc and manganese, zinc and molybdenum, respectively. In the experiment, were made 4 applications of resistance inducers (phenological stages V3, V6, R1 and R5.1) and two of the fungicide (phenological stages R1 and R5.1). The characteristics evaluated were: severity of downy mildew (Peronospora manshurica), powdery mildew (Microsphaera diffusa), rust (P. pachyrhizi), final disease cycle (DFC), defoliation, yield components, yield and germination and health of harvested seeds. With the data of severity calculated the area under the disease progress curve (AUDPC). Substitutes controlled the mildew, but had no effect on powdery mildew, rust, DFC and defoliation. The fungicide treatment was the one who controlled the rust, powdery mildew, DFC and defoliation. Cultivate the yield components those affected by the treatments were the number of pods per plant and thousand kernel weight. Treatment with fungicide had the highest productivity. Defoliation was strongly correlated with the PMG, emphasizing the importance of maintaining the leaf area to ensure grain filling. Foliar treatments and the best treatments NK fertilizer and fungicide affected the germination and seed health.
Keywords: indução de resistência; Glycine max, Phakopsora pachyrhizi; Sclerotinia sclerotiorum e Rhizoctonia solani; doenças; induction of resistance; Glycine max; Phakopsora pachyrhizi; Sclerotinia sclerotiorum e Rhizoctonia solani; diseases; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA